The Ecosystem of VLE Implementation in Saudi Secondary Education: Bridging the Gap Between Infrastructure and Pedagogy - Ahmed Y. Alhujayri, Israa (Emerging Frontiers Library for The American Journal of Interdisciplinary Innovations and Research, 2024)
The integration of Virtual Learning Environments (VLEs) is a cornerstone of Saudi Arabia’s Vision 2030 educational reforms. However, the mere acquisition of platforms like Classera does not guarantee pedagogical transformation. This study investigates the implementation dynamics of Classera across five secondary schools in Saudi Arabia, utilizing a mixed-methods approach comprising surveys with 91 teachers, interviews with leadership, and classroom observations. The analysis reveals a dichotomy in usage: while the platform successfully streamlines resource sharing and administrative communication, it remains underutilized for advanced, interactive learning. We argue that successful VLE adoption is contingent upon a supportive ecosystem involving robust ICT infrastructure, continuous professional development, and proactive school leadership. Without these pillars, VLEs serve primarily to digitize traditional practices rather than revolutionize learning.